Sustainability of healthcare innovations (SUSHI): long term effects of two implemented surgical care programmes (protocol) - Ament Stephanie M C; Gillissen Freek; Maessen José M C; Dirksen Carmen D; van der Weijden Trudy; von Meyenfeldt Maarten F (BMC, 2012)
Abstract Background Two healthcare innovations were successfully implemented using different implementation strategies. First, a Short Stay Programme for breast cancer surgery (MaDO) was implemented in four early adopter hospitals, using a hospital-tailored implementation strategy. Second, the Enhanced Recovery After Surgery (ERAS) programme for colonic surgery was implemented in 33 Dutch hospitals, using a generic breakthrough implementation strategy. Both strategies resulted in a shorter hospital length of stay without a decrease in quality of care. Currently, it is unclear to what extent these innovative programmes and their results have been sustained three to five years following implementation. The aim of the sustainability of healthcare innovations (SUSHI) study is to analyse sustainability and its determinants using two implementation cases. Methods This observational study uses a mixed methods approach. The study will be performed in 14 hospitals in the Netherlands, from November 2010. For both implementation cases, the programme aspects and the effects will be evaluated by means of a follow-up measurement in 160 patients who underwent breast cancer surgery and 300 patients who underwent colonic surgery. A policy cost-effectiveness analysis from a societal perspective will be performed prospectively for the Short Stay Programme for breast cancer surgery in 160 patients. To study determinants of sustainability key professionals in the multidisciplinary care processes and implementation change agents will be interviewed using semi-structured interviews. Discussion The concept of sustainability is not commonly studied in implementation science. The SUSHI study will provide insight in to what extent the short-term implementation benefits have been maintained and in the determinants of long-term continuation of programme activities.